Epidemiology and management of chronic hepatitis E infection in solid organ transplantation: a comprehensive literature review. (1st July 2013) - Zhou, Xinying; de Man, Robert A.; de Knegt, Robert J.; Metselaar, Herold J.; Peppelenbosch, Maikel P.; Pan, Qiuwei
SUMMARY: Hepatitis E virus (HEV) infection has emerged as a global public health issue. Although it often causes an acute and self‐limiting infection with low mortality rates in the western world, it bears a high risk of developing chronic hepatitis in immunocompromised patients with substantial mortality rates. Organ transplant recipients who receive immunosuppressive medication to prevent rejection are thought to be the main population at risk for chronic hepatitis E. Therefore, there is an urgent need to properly evaluate the clinical impact of HEV in these patients. This article aims to review the prevalence, infection course, and management of HEV infection after solid organ transplantation by performing a comprehensive literature review. In addition, an in‐depth emphasis of this clinical issue and a discussion of future development are also presented. Copyright © 2013 John Wiley & Sons, Ltd.